2013
DOI: 10.3748/wjg.v19.i15.2293
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal anastomotic leakage: Aspects of prevention, detection and treatment

Abstract: All colorectal surgeons are faced from time to time with anastomotic leakage after colorectal surgery. This complication has been studied extensively without a significant reduction of incidence over the last 30 years. New techniques of prevention, by innovative anastomotic techniques should improve results in the future, but standardization and "teachability" should be guaranteed. Risk scoring enables intra-operative decision-making whether to restore continuity or deviate. Early detection can lead to reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
95
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 24 publications
7
95
1
4
Order By: Relevance
“…This could translate into fewer days of hospitalization (both in the ICU and on the ward postoperatively) and, therefore, lower hospital costs. The data obtained by us, as well as those in the literature, show that CRP may foreshadow the occurrence of a complication long before its clinical and imaging manifestation (1.5 days versus 4 days), allowing early diagnosis and aggressive treatment (6). For new digestive sutures we also introduced leukocyte count monitoring from peritoneal drainage fluid, along with CRP and CBC.…”
Section: Resultsmentioning
confidence: 99%
“…This could translate into fewer days of hospitalization (both in the ICU and on the ward postoperatively) and, therefore, lower hospital costs. The data obtained by us, as well as those in the literature, show that CRP may foreshadow the occurrence of a complication long before its clinical and imaging manifestation (1.5 days versus 4 days), allowing early diagnosis and aggressive treatment (6). For new digestive sutures we also introduced leukocyte count monitoring from peritoneal drainage fluid, along with CRP and CBC.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple numbers of stapler firings during rectal division and double-stapled colorectal anastomosis significantly increases the incidence of anastomosis leak and strictures, as shown in the study of Ito et al [10]. Surgeon's experience and, in particular, low-case volume per center (<20 per year) are also involved in AL etiology [9]. Mechanical staplers are nowadays widely used in GI surgery [5,6]; notwithstanding the important diffusion of these instruments, there are very few published articles about their mechanical characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…It leads to prolonged hospital stay, increased morbidity, mortality, and medical costs [4]. Anastomotic failure depends on various parameters, ranging from patient to surgical technique and instruments and surgeon's experience [9]. Well-recognized patient risk factors for AL are localization (increased incidence on the distal tract, highest on the lower rectum), previous radiotherapy (locally advanced rectal cancer), emergency operation, male sex, advanced age, diabetes mellitus, vasculopathy, obesity, chronic obstructive pulmonary disease, denutrition, chronic corticosteroidal use, and unknown vascular abnormalities [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Several studies have reported leakage incidence after surgeries including esophageal surgeries (7%), 2 colorectal surgeries (8.7%), 3 pancreatic surgeries (0-25%), 4 laparoscopic sleeve gastrectomy (1.4-2.5%), 5 and Roux-en-Y gastric bypass surgeries (0.7-20%). 6 It poses a challenge for surgeons worldwide as it is difficult to manage, is usually associated with long hospital stay, and has high mortality rates that range from 4.8 to 75%.…”
mentioning
confidence: 99%